Online teaching efficacy and its determinants among Chinese college teachers during the COVID-19 pandemic online teaching - Li, Shifeng; Xu, Qiongying; Dang, Baobao (Frontiers in Education, 2024)
To minimize the impact of the COVID-19 pandemic on education, countries around the world have turned to online teaching and learning. However, this sudden change also challenges teachers' teaching competence and efficacy. This study investigated online teaching efficacy and its determinants among Chinese college teachers during the COVID-19 pandemic online teaching. Two hundred and seventeen Chinese college teachers who engaged in online teaching during the pandemic participated in an online survey focusing on online teaching efficacy. The results showed that the overall online teaching efficacy of college teachers was relatively high. While demographics such as gender, age, teaching experience, academic title, highest degree attained, and area of expertise did not significantly impact online teaching efficacy, relevant experiences in online teaching -such as prior online course instruction, participation in online teaching training programs or seminars, and collaborative discussions with colleagues -were found to enhance online teaching efficacy.Universities should quickly adapt to this change and build a professional development support system for faculty in online teaching.